Pemenuhan Hak Konsumen dalam Penggunaan Kuota Internet Sistem FUP - Moh. Ismail Mantolongi; Weny Almoravid Dungga; Mohamad Taufiq Zulfikar Sarson (Jembatan Hukum : Kajian ilmu Hukum, Sosial dan Administrasi Negara, 2025)
This study aims to determine and analyze the form of fulfillment of consumer rights of IndiHome service provider users in the Laws and Regulations in Indonesia due to the FUP system and the responsibility of the IndiHome provider towards consumers due to the FUP system. This study is classified as normative research with a historical approach, comparative approach and conceptual approach. Legal materials are collected through document studies, then analyzed prescriptively. The results of the study indicate that consumer rights and the responsibilities of business actors, namely Indihome, have been regulated in Law No. 8 of 1999 concerning Consumer Protection. Although it has been regulated in the Laws and Regulations, this situation is no longer effective because when an error occurs, Indihome can be released from its responsibility. For this reason, it is necessary to revise Article 27 letter b of Law No. 8 of 1999 concerning Consumer Protection.